Broadband, Beam-Steering Asymmetric Stacked Microstrip Phased Array with Enhanced Front-to-Back Ratio - Melih Türk; Fikret Tokan, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
The backward radiation is a critical problem that may cause breakdown of the front-end circuits that are integrated behind the antenna. Thus, antennas having high Front to Back Ratio (FBR) are required. For phased arrays, the back lobe suppression is required for all scanning angles at all frequencies of the band. In this work, a stacked patch linear array with asymmetric configuration is proposed. It is capable of scanning the beam in ±40º with less than 1.34 dB scanning loss. Due to the usage of probe-fed stacked patches as the antenna elements, impedance matching in 8-10 GHz is achieved. More than 30 dB FBR is obtained for broadside radiation. It is above 20 dB when the beam is steered to θ = 40º. This is valid for all frequencies of the band. A prototype is fabricated and measured. Higher than 38 dB FBR is observed. With its broadband, high FBR and low scanning loss, the proposed asymmetrical stacked patch phased array is suitable as radar and base station antenna.